OPTIMIZING SCRAP FABRIC UTILIZATION INTO MASKS AND DOORMATS FOR ECONOMIC EMPOWERMENT OF THE PKK WOMEN’S GROUP IN KLETEK VILLAGE, TAMAN DISTRICT, SIDOARJO - Budi Purwantiningsih; A’ilatul Zahroh; Febriarsita Eka Sasmita; Hanik Yuni Alfiyah; M. Amin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study aims to provide training in making masks and doormats from scrap fabric to the PKK group in Kletek Taman Sidoarjo Village. The training was conducted in three main phases: 1) Socialization and FGD, 2) Demonstration and Practice, 3) Packaging and Marketing The first phase was conducted with community leaders, village heads, and the PKK team from Unsuri Surabaya to identify community potential and plan activities. The second phase focused on training skills in mask and doormat production, where participants were taught innovative designs and patterns for masks, as well as techniques for creating attractive doormats with new motifs and color combinations. The third phase included product packaging and branding to enhance competitiveness. Additionally, participants were trained in digital marketing using social media and websites to expand market reach. The goal is for participants to apply new skills in product creation and improve marketing through digital platforms.